Comparison of High Versus Low Intra-Peritoneal Carbon Dioxide Pressure on Abdominal Pain, Hemodynamic Symptoms and Liver Function Tests in Patients Undergoing Laparoscopic Cholecystectomy - Aamir Ghazanfar, Afifa Asghar, Aamir Ghazanfar, Afifa Asghar (Journal of Rawalpindi Medical College, 2019)
Background: To compare the intensity of abdominal pain, hemodynamic symptoms and liver function tests due to usage of low and high-pressure CO2 in individuals undergoing laparoscopic cholecystectomy (LC). Methods: A randomized double blind clinical trial was conducted on a sample of 60 patients who were undergoing LC. Patients within the age limit of 20-70 years were incorporated in the study. Patients were separated into 2 groups; the first group was administered to a PaCO2 of 7-10 mmHg while the second group was administered to a PaCO2 of 12-14 mmHg. The abdominal pain, liver function tests and hemodynamic symptoms were checked. Data analysis was done using SPSS version 19.0. Results:A significant statistical variation (p< 0.05) was seen among systolic blood pressure of the two groups. Similarly a statistically significant variation was observed among the mean of heart rates. The mean heart rate of the high-pressure group was high during surgery and 1 h after operation (P < 0.05). High pressure group had high value of abdominal pain. Conclusion: Due to quality and less side effects, low-pressure LC technique is better than high- pressure laparoscopic cholecystectomy.